Increased Hydration Can Be Associated with Weight Loss - Thornton, Simon N. (Frontiers in Nutrition, 2016)
This mini-review develops the hypothesis that increased hydration leads to body weight loss, mainly through a decrease in feeding and a loss of fat through increased lipolysis. The publications cited come from animal, mainly rodent, studies where manipulations of the central and/or the peripheral renin-angiotensin system lead to an increased drinking response and a decrease in body weight. This hypothesis derives from a broader association between chronic hypohydration (extracellular dehydration) and raised levels of the hormone angiotensin II (AngII) associated with many chronic diseases such as obesity, diabetes, cancer and cardiovascular disease. Proposed mechanisms to explain these effects involve an increase in metabolism due to hydration expanding cell volume. The results of these animal studies often can be applied to the humans. Human studies are consistent with this hypothesis for weight loss and for reducing the risk factors in the development of obesity and type 2 diabetes.